APPLICATION OF POWDER HIGH-SPEED STEEL AS ANTIFRICTION MATERIAL - M. Beznak; A. S. Chaus; M. Bajchichak (Литьë и металлургия)
Influence of molybdenum disulfide additives on antifriction characteristics of powder fast-cutting steel produced by means of hot hydrostatic compression is studied.